Peningkatan Kapasitas Sumber Daya Manusia Petani Ciawi Melalui Pelatihan Manajemen Kelompok dan Literasi Digital - Dematria Pringgabayu; Ratri Wahyuningtyas; Syahputra Syahputra (Apik Cahaya Ilmu, 2026)
The development of the quality of Human Resources (HR) is a decisive factor in the modernization of the agribusiness sector in the era of digital transformation. This community service activity aims to increase the capacity of human resources of the Mukti Sadaya Organic Farmer Economic Institution (KEP) in Tasikmalaya Regency. The main problems faced by target partners include non-functional organizational structures, overlapping conventional division of labor, manual administration, and the use of devices that have not been optimized to support group productivity. The implementation method used is Participatory Capacity Building through the stages of organizational diagnosis, group management workshops, applied digital literacy training, and intensive mentoring. The results of this activity show that there is a real increase in professionalism, institutional governance and technological proficiency for 24 members of farmer groups. The benefits obtained include the realization of a systematic organizational structure, the preparation of internal Standard Operating Procedures (SOPs), and the implementation of a cloud storage-based digital administration system. The conclusion of this activity emphasizes that the integration between strengthening group internal management and mastery of digital literacy is the main foundation in creating an independent, transparent, and ready farmer organization to face modern economic dynamics.